Improving removal rate and efficiency of As(V) by sulfide from strongly acidic wastewater in a modified photochemical reactor. Issue 15 (3rd July 2022) - Kong, Linghao; Wang, Yuchen; Hu, Xingyun; Peng, Xianjia; Xia, Zhilin; Wang, Jianbing
ABSTRACT: Employing ultraviolet light to enhance the removal of As(V) by sulfide (S(-II)) from strongly acidic wastewater is a potential method. However, we found the arsenic trisulfide (As2 S3 ) and elemental sulfur (S8 ) particles formed in this method not only vastly hinder light transmission in the wastewater but also undergo light-induced redissolution, leading to a decrease in removal rate and efficiency of As(V). Herein, As(V) removal by sulfide from strongly acidic wastewater was performed in a modified photochemical reactor to weaken the effect of the formed particles on As(V) removal. It was found that in this study, the formed particles could be efficiently removed from the photoreactor by three operations, i.e. circulation-filtration, septum setting, and lamp sleeve cleaning. The removal of As(V) was approximately 11-fold faster than that without three operations, saving 90.9% of the reaction time and 89.4% of energy consumption. The removal efficiency of As(V) also increased through weakening the light-induced redissolution of the formed particles. This study facilitates the practical application of the UV light promoted As(V) removal technology and also provides a new method to lessen the light-blocking effect in the particle-forming photochemical reaction systems. GRAPHICAL ABSTRACT: UF0001